Changing predictors of statin initiation in US women over two decades. Issue 3 (19th December 2018) - Kinsey, Tracy L.; Stürmer, Til; Poole, Charles; Rothman, Kenneth J.; Glynn, Robert J.
Abstract: Purpose: To describe changing roles of predictors of statin initiation before and after incident coronary heart disease, and before and after publication of National Cholesterol Education Program Adult Treatment Panel‐III (ATP‐III) guidelines in a cohort of US women. Methods: We identified 34 382 women enrolled into the Women's Health Study from 1993 to 1995 and followed up until 2012. Proportions of previous nonusers initiating statins were described over time. We used multivariable linear regression models to estimate adjusted initiation proportion differences (IPDs) for initiation overall, separately before and after incident coronary heart disease, and separately for ATP‐II and ATP‐III time periods. Results: Key predictors of initiation overall were self‐reported total cholesterol, and previous incident coronary heart disease, cerebrovascular disease, and diabetes. Adjusted IPDs (percentage) for total cholesterol > 240 vs <200 mg/dL were 7.5 (95% confidence interval [CI], 7.0‐8.0) and 9.3 (95% CI, 8.7‐9.9) during ATP‐II and ATP‐III time periods, respectively. Adjusted IPDs in women with diabetes were 7.0 (95% CI, 6.3‐7.8) and 11.9 (95% CI, 6.7‐17.0) for primary and secondary prevention, respectively, and 3.1 (95% CI, 2.1‐4.0) and 9.2 (95% CI 8.2‐10.2) for before and after ATP‐III, respectively. Conclusions: Secular trends reflected evolution toward risk factor‐based treatment indications for statin initiation with increased initiation among diabetics and women with normal and borderline cholesterol. The role of serum cholesterol changed over time, though the character was scale (multiplicative vs additive) dependent. In pharmacoepidemiologic studies of statins, strength of confounding by important variables sometimes unmeasured in claims data, such as cholesterol level, may be calendar time dependent.